Posisi Media dalam Membentuk Budaya “Perkawinan Politik” Sulawesi Tenggara Daratan dengan Kepulauan Sulawesi Tenggara pada Pemilihan Gubernur Sulawesi Tenggara - Fahmy Fotaleno; Denny Setiawan Batubara (LITERATUS, 2023)
The objectives of this research are: This study aims: (1) to determine the role of the media in shaping the culture of "political marriage" between the mainland and the islands in the Southeast Sulawesi Governor Election and (2) the model for selecting strategies in the culture of "political marriage" between the mainland and the islands of Southeast Sulawesi in the election of the governor of Southeast Sulawesi. This research is a qualitative descriptive study. Data obtained through observation, interviews and media documentation. Information was obtained from various sources who were considered active and directly involved in the direct election for the Governor and Deputy Governor of Southeast Sulawesi. In the Southeast Sulawesi Pilgub event, the role of the media is quite high in leading public opinion and also the elite to "marry" the pair of figures from the Southeast Sulawesi and Southeast Sulawesi Islands. This practice is deliberately carried out to as much as possible the identity of the people of Southeast Sulawesi who are geographically divided into people who live and live in the Southeast Sulawesi region and people in Southeast Sulawesi feel represented in this pair. The distribution of discourse to society is carried out strategically by the media, be it print media, online media and electronic media.